2020
DOI: 10.1186/s40677-020-00169-5
|View full text |Cite
|
Sign up to set email alerts
|

A late Holocene record of marine high-energy events along the Atlantic coast of Morocco: new evidences from the Tahaddart estuary

Abstract: The Atlantic coast of Morocco has been exposed to marine submersion events from storm surges and tsunamis which have resulted in human and economic losses. The absence of long term records for these hazards makes it difficult to trace their behavior through time, which is the first step to prepare proactive adaptation strategies for events that may happen in the future. In this paper, we present a late Holocene record of marine submersion events along the Atlantic coast of Morocco using a 2.7 m sediment core s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…Several attempts to model the effects of these events and to estimate the risk to human life and goods, show that the region is widely exposed if similar events were to recur (Omira et al 2010;Atillah et al 2011;Renou et al 2011;Mellas et al 2012;Moussaoui et al 2017;Ramalho et al 2018). In addition to historical documents, material evidence (geomorphic and sedimentary indices) for tsunamis or high energy events in Morocco have been found in many sites alongside the Moroccan Atlantic coast: (1) in Larache and Rabat (Medina et al 2011), (2) Tahadart estuary (Talibi et al 2016;Khalfaoui et al 2020) and (3) close to the Loukkos river mouth, (Mhammdi and Medina, 2015). According to Soyris (1755), the Lisbon earthquake of 1755, the intensity of which reached VIII-XI on the Mercali scale, produced a large tsunami wave that affected northern Morocco, with El-Jadida city being one of the most impacted (Levret 1991).…”
Section: Tsunamis In Moroccomentioning
confidence: 99%
“…Several attempts to model the effects of these events and to estimate the risk to human life and goods, show that the region is widely exposed if similar events were to recur (Omira et al 2010;Atillah et al 2011;Renou et al 2011;Mellas et al 2012;Moussaoui et al 2017;Ramalho et al 2018). In addition to historical documents, material evidence (geomorphic and sedimentary indices) for tsunamis or high energy events in Morocco have been found in many sites alongside the Moroccan Atlantic coast: (1) in Larache and Rabat (Medina et al 2011), (2) Tahadart estuary (Talibi et al 2016;Khalfaoui et al 2020) and (3) close to the Loukkos river mouth, (Mhammdi and Medina, 2015). According to Soyris (1755), the Lisbon earthquake of 1755, the intensity of which reached VIII-XI on the Mercali scale, produced a large tsunami wave that affected northern Morocco, with El-Jadida city being one of the most impacted (Levret 1991).…”
Section: Tsunamis In Moroccomentioning
confidence: 99%
“…Usually, the DeltaR value can be estimated by comparing 14 C dates obtained on pairs of contemporary marine and continental organisms, collected for example at the same depth in the same sediment core (or trench), or found at the same coastal archaeological site. In the Tahaddart estuary (NW of Morocco), Khalfaoui et al (2020) tried to estimate this value using a pair of contemporary wood and marine shell, collected from the same depth in one of the studied cores. The authors found a value of -75±20 years, which is relatively close to the one obtained by Martins and Soares (2013) for the Andalusian coast in Spain (-108 ± 31 years).…”
Section: Gaps and Needsmentioning
confidence: 99%
“…The authors found a value of -75±20 years, which is relatively close to the one obtained by Martins and Soares (2013) for the Andalusian coast in Spain (-108 ± 31 years). However, the value obtained by Khalfaoui et al (2020) There is a great need to work in partnership with local historians and archaeologists to better understand the impact of these extreme events on the local population, which has occupied the Moroccan coasts since the Neolithic phase. During the Roman period, trade activities, based on fishing, salt and garum production were probably affected by these disasters.…”
Section: Gaps and Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 10 years, several coastal sites were investigated for sedimentary traces left by marine submersions, in the hope of dating them and filling the information gap regarding these natural hazards. Multiple sites with sedimentary evidences of these events were identified along the Moroccan coasts, in the form of boulders (Medina et al 2011) and fine-grained sediments (typically sand-sized) (Mhammdi et al 2015;Raji et al 2015;El Talibi et al 2016;Khalfaoui et al 2020). Despite this effort, the number of studies is still low compared to the nearby Iberian coasts, which are confronted with the same natural disasters.…”
mentioning
confidence: 99%